Diaphragm injuries in a mature trauma system: still a diagnostic challenge - S. Karhof; R. K. J. Simmermacher; P. Gerbranda; K. J. P. van Wessem; L. P. H. Leenen; F. Hietbrink (Frontiers in Surgery)
BackgroundA traumatic diaphragm defect is a rare injury. A missed diaphragm injury may cause serious morbidity and mortality. Detection rate during the first assessment of trauma patients is notoriously low. However, important improvements in imaging modalities were developed. The aim of this study was to analyze traumatic diaphragm injuries in relation to diagnostic tools, therapeutic interventions and outcome over the past two decades.MethodsA retrospective analysis was performed of all trauma patients with traumatic diaphragm injuries between 2000 and 2018 at a level I trauma center. Data collected were baseline characteristics, diagnostics that were performed, treatment given and follow-up.ResultsA total of 47 patients with traumatic diaphragm injuries were evaluated. The majority of injuries was seen following blunt trauma (72%). Mortality was 21%, mainly due to concomitant injuries. One patient died due to the consequences of an unrecognized diaphragm injury. In 29 cases (62%) the injury was diagnosed pre-operatively through imaging, with the remaining being diagnosed during laparotomy. In 11 patients (35%) the diaphragmatic injury was not seen on a pre-operative CT-scan. Postoperative complications occurred in 19 patients, mostly of pulmonary origin (i.e., pneumonia). No recurrences were reported.ConclusionThis study confirms diaphragm injuries are infrequent injuries, with high mortality. Even more, despite major improvement in diagnostic modalities over the past 2 decades, the algorithm for detection of diaphragmatic injuries has not changed nor has its outcome. Although the incidence is low, since consequences are severe, it is important to have a high index of suspicion in abdominal trauma, even in a non-conclusive CT-scan.